Aerial additive building manufacturing: three-dimensional printing of polymer structures using drones. Issue 1 (14th July 2017) - Dams, Barrie; Sareh, Sina; Zhang, Ketao; Shepherd, Paul; Kovac, Mirko; Ball, Richard J.
Abstract : This paper describes the first aerial additive building manufacturing system developed to create and repair civil engineering structures remotely using polymers extruded from unmanned aerial robots (drones). The structural potential of three commercially available expanding polyurethane foams of varying density (LD40, Reprocell 300 and Reprocell 500), and their feasibility for deposition using an autonomous flying dual-syringe device is described. Test specimens consisting of one and two layers, with horizontal and vertical interfaces, were mechanically tested both parallel and perpendicular to the direction of expansion. LD40 specimens exhibited ductile failure in flexural tests and provided evidence that the interfaces between layers were not necessarily regions of weaknesses. Hand-mixed specimens of Reprocell 500 possessed compressive strengths comparable to those of concrete and flexural strengths similar to those of the lower range of timber, though they exhibited brittle failure. There are challenges to be faced with matching the performance of hand-mixed specimens using an autonomous dual-syringe deposition device, primarily concerning the rheological properties of the material following extrusion. However, the device successfully imported and deposited two liquid components, of varying viscosity, and maintained correct mixing ratios. This work has demonstrated the structural and operational feasibility of polyurethane foam as a viable structural material for remote three-dimensional printing using drones.